2020
DOI: 10.1002/ccr3.3610
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of ectopic retrosternal goiter

Abstract: It is important for the clinician to be familiar with interpreting a variety of radiological modalities that provide vital information that will aid in the preoperative planning, counseling, and subsequent management of patients with retrosternal goiter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…This happened in one of our patients, whereas postoperatively the final pathological result declared that the goiter had a large malignant component in the chest portion (2) . Chia et al (16) revealed that the incidence of malignancy in substernal goiters is almost the same as that found in cervical goiters (3% to 21%). In our series, the incidence of malignancy was 4.7% and was diagnosed postoperatively as discussed before.…”
Section: Characteristics Of Rsgmentioning
confidence: 76%
See 3 more Smart Citations
“…This happened in one of our patients, whereas postoperatively the final pathological result declared that the goiter had a large malignant component in the chest portion (2) . Chia et al (16) revealed that the incidence of malignancy in substernal goiters is almost the same as that found in cervical goiters (3% to 21%). In our series, the incidence of malignancy was 4.7% and was diagnosed postoperatively as discussed before.…”
Section: Characteristics Of Rsgmentioning
confidence: 76%
“…Blind maneuvers to attempt to dislocate the mediastinal component of the goiter into the neck via passage of a Foley's catheter into the mediastinum, morcellation of the RSG, and insertion of strong silk sutures into the cervical goiter to apply traction from the neck are discouraged due to the risk of uncontrollable hemorrhage and the possibility of injury to adjacent critical structures in the thoracic inlet (1,7,13,16) .…”
Section: Characteristics Of Rsgmentioning
confidence: 99%
See 2 more Smart Citations
“…Goiter is a diffuse or localized thyroid gland enlargement. 1 It is more common in women and is associated with an increase in thyroid hormones and, subsequently, an increase in TSH, which causes the enlargement of the thyroid tissue. It is usually in the neck, but sometimes it spreads into the thorax and mediastinum.…”
Section: Introductionmentioning
confidence: 99%